Implications of the integration process of the administrative records of criminality between the SPOA (Oral Accusatory Criminal System) of the Attorney General’s Office (FGN) and the SIEDCO (Statistical, Delinquency, Offenses and Operations Information System) of the National Police of Colombia (PONAL), and the implementation of the “¡ADenunciar!” app on crime figures. - Jair David Rodríguez Ortega; Lorena del Pilar Caro Zambrano; Daniel Mejía Londoño; Mauricio Romero Hernández; Franney Campos Méndez (Revista Criminalidad)
In 2017, the Information System [SIEDCO] of the National Police [PONAL], one of the main sources of criminality information in the country, experienced two important changes in the consolidation of its crime figures. The first, was the integration into SIEDCO of the administrative records of complaints of the Attorney General’s Office [FGN] Criminal System [SPOA]. The latter was the implementation of the “¡ADenunciar!” (“ReportACrime!”) app, an application that allows citizens to file some complaints through the FGN’s Internet webpage. These changes have generated important variations in the series of data that measure the criminality registered in the country, which prevent the comparability of crime figures in recent years in the country.